Hydrodynamic optimization of the UGEN: Wave energy converter with U-shaped interior oscillating water column. (September 2016) - Ribeiro e Silva, S.; Gomes, R.P.F.; Falcão, A.F.O.
Abstract: The paper presents an optimization design procedure for wave energy converters (WECs) of the oscillating water column (OWC) type, where main dimensions and geometry of the wave-floater and OWC main characteristics for a given Power-Take-Off (PTO) are selected to attain the most cost effective power generation solution off the Portuguese west coast (design-point). For optimization purposes, two algorithms that do not require the function gradient (Genetic Algorithm and COBYLA) have been proposed to solve this typical multi-dimensional, single objective (maximization of the produced electrical energy or maximization of the annual profit) problem in order to take into account not only the efficiency of the WEC, but also the most relevant operational and manufacturing aspects of these floating electro-mechanic devices. The annual averaged power output scatter diagrams at the design-point based on computer simulations are presented for the Wells turbine equipping the optimized wave-floater. A direct comparison between the total mean power of the optimized UGEN and that same power extracted by the baseline configuration considering all the sea states in one year at the design point is also presented in this paper in order to demonstrate the advantages of this design tool.